Energy and exergy analyses of ammoniated salts based thermochemical sorption heat storage system. (1st August 2022) - Zhang, Hong; Yan, Ting
Abstract: Thermal energy storage (TES) is a critical technology to improve energy infrastructures by harvesting low-grade heat and renewable energy. Thermochemical sorption heat storage (TSHS) is considered to be the most promising TES technology due to excellent energy storage performance and flexible working mode. Ammoniated salts with high adsorption capacity and reaction enthalpy are favorable heat storage materials. Using energy and exergy analyses to evaluate heat storage performance is conducive to the highly utilization of the energy and optimization of the energy system. In this work, the thermodynamic performance of the sorption heat storage cycle with ammoniated salts was surveyed through the energy and exergy analysis methods. The general efficiencies of four salts for the sorption heat storage during charging, discharging and the whole system were estimated. Results showed that SrCl2 and SrBr2 are expected to be the most promising materials for the sorption heat storage among the four chemical salts. The overall energy efficiencies of SrCl2 -NH3 and SrBr2 -NH3 sorption heat storage systems are 39.8% and 41.6%, respectively, and the corresponding overall exergy efficiency are 17.3% and 13%. The Carnot factor-induced efficiency of SrCl2 -NH3 and SrBr2 -NH3 sorption heat storage systems are 0.123 and 0.087, respectively. Highlights: The general efficiency of thermochemical sorption heat storage system has been evaluated. Energy and exergy analysis formulas for sorption heat storage are established. The Carnot factor-induced efficiency of SrCl2 -NH3 sorption heat storage systems is 0.123. SrCl2 -NH3 as working pair won the highest overall exergy efficiency of 17.3%.